2019
DOI: 10.1002/prp2.485
|View full text |Cite
|
Sign up to set email alerts
|

A structured literature review of interventions used in the management of nonalcoholic steatohepatitis (NASH)

Abstract: Nonalcoholic steatohepatitis ( NASH ) is a chronic, progressive disease, that can advance to fibrosis, cirrhosis, and hepatocellular carcinoma. Despite being a leading cause of liver transplantation, there are no approved pharmacological treatments. Our aim was to identify literature on management options in NASH . Our structured review of interventions treating NASH patients from English language publications between 1 January 2007 and 25 Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
(181 reference statements)
0
17
0
Order By: Relevance
“…[ 158 ] However, in patients with progressing to advanced fibrosis lifestyle interventions alone are not sufficient. [ 159 ]…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…[ 158 ] However, in patients with progressing to advanced fibrosis lifestyle interventions alone are not sufficient. [ 159 ]…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…Regarding VCAM-1, it has also been recently validated as an accurate biomarker of fibrosis in NASH patients. 42 Furthermore, ASK1/MAP3K5 has been largely described in the literature as a pharmacological target for NASH disease treatment [43][44][45] and, interestingly, its up-regulation is observed in our human 3D NASH model (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 57%
“…Regarding VCAM-1, it has also been recently validated as an accurate biomarker of fibrosis in NASH patients (Lefere et al, 2017). Furthermore, apoptosis signaling kinase 1 (ASK1/MAP3K5) has been largely described in the literature as a pharmacological target for NASH disease treatment (Povsic et al, 2019, Connolly et al, 2018, Drescher et al, 2019 and, interestingly, its upregulation is observed in our human 3D NASH model (Table S2).…”
Section: Discussionmentioning
confidence: 67%